Mucopolysaccharidosis Type VI in a Great Dane Caused by a Nonsense Mutation in the ARSB Gene. Issue 2 (March 2018) - Wang, Ping; Margolis, Carol; Lin, Gloria; Buza, Elizabeth L.; Quick, Scott; Raj, Karthik; Han, Rachel; Giger, Urs
Mucopolysaccharidoses are inherited metabolic disorders that result from a deficiency of lysosomal enzymes required for the catabolism of glycosaminoglycans. Lysosomal glycosaminoglycan accumulation results in cell and organ dysfunction. This study characterized the phenotype and genotype of mucopolysaccharidosis VI in a Great Dane puppy with clinical signs of stunted growth, facial dysmorphia, skeletal deformities, corneal opacities, and increased respiratory sounds. Clinical and pathologic evaluations, urine glycosaminoglycan analyses, lysosomal enzyme assays, and ARSB sequencing were performed. The urine mucopolysaccharide spot test was strongly positive predominantly due to the accumulation of dermatan sulfate. Enzyme assays in leukocytes and tissues indicated a deficiency of arylsulfatase B (ARSB) activity. Histologic examination revealed cytoplasmic vacuoles in many tissues. Analysis of the exonic ARSB DNA sequences from the affected puppy compared to the published canine genome sequence revealed a homozygous nonsense mutation (c.295C>T) in exon 1, replacing glutamine with a premature stop codon (p.Gln99*), predicting no enzyme synthesis. A polymerase chain reaction–based restriction fragment length polymorphism test was established to assist with the clinical diagnosis and breeding of Great Danes. This genotyping test revealed that the clinically healthy parents and some other relatives of the puppy were heterozygous for the mutant allele, but all 200 clinically healthy dogs screened including 15 Great Danes were homozygous for the normal allele. This ARSB mutation is the fourth identified genetic variant causing canine mucopolysaccharidosis VI. Mucopolysaccharidosis VI is the first lysosomal storage disorder described in Great Danes but does not appear to be widespread in this breed.